PENDIDIKAN KARAKTER MELALUI SATUA BALI - Wayan Wira Dharma (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2020)
ABSTRACTSatua Bali has a huge influence in shaping children's character, so that children can have characters that are firmly rooted in culture. Character building is done by listening to folk tales which become local wisdom in the form of satua. The activity of appreciating satua is closely related to the exercise of sharpening feelings, reasoning, and imagination, as well as sensitivity to society, culture, and the environment. Children are expected to be able to enjoy, appreciate, understand, and take advantage of literary works in general and satua in particular to develop their personality, broaden their horizons of life, and increase their knowledge and language skills. In attitude and behavior, human character puts forward mental or moral qualities and focuses on how to apply good values, in the form of actions or behavior. Satua can be useful as a means of character education and as a successor to the values and spirit of local wisdom to preserve the sustainability of the story itself. Keywords: Satua Bali, Character Education